Karakteristik Responden dalam Penggunaan Jaminan Kesehatan Pada Era BPJS di Puskesmas Cisoka Kabupaten Tangerang Januari-Agustus 2015 - Sarah Nadia Rahmayanti; Tri Ariguntar (Universitas Muhammadiyah Yogyakarta, 2017)
Puskesmas is the main of the program bpjs health. Center role crucial where be the basic health services acting as first contact to the community .The main objective of BPJS is ensure that participants receive the healthcare benefit and the protectionneeds basic health, includes promotive, preventive, curative and rehabilitative treatments.Objectives in this study isto get a profile patient visits Puskesmas Cisoka Tangerang in the era of BPJSjanuary to august 2015. The method used in this study is descriptive with cross sectional method. The respondents in this study is the total patient visits puskesmas cisoka. A measuring instrument in study is data secondary and analysis of data univariat. The result of study has reached 104 respondents. Most patients who visited puskesmas is outpatients as 80,8 %, where 61,5 % of this percentage are women.Health insurance in use outpatients the majority pay own ( patients ) of 78,5 % , where 20,2 % outpatients using health insurance bpjs .The diagnosis of the total visits puskesmas patients suffering ispa the majority of 19,2 % , where ispa is also the percentage of the majority of outpatients .Meanwhile majority of patients diarrhea acute as many as 40 %. The conclusion on this study isvisits patients at puskesmas cisoka most of the patients outpatient with most of patients use health service scheme pay own ( a patient public with the diagnosis most outpatient is tract , while in-patient is acute diarrheal.